MEDIEN - WISSEN - BILDUNG: Freie Bildungsmedien und Digitale Archive - Stalder, Felix (MEDIEN - WISSEN - BILDUNG, 2014)
Ever since digital technologies became widespread, the increasing capacities of storing, exchanging and sharing of information have given rise to optimistic scenarios of an egalitarian information society as well as to pessimistic views of a technocratic surveillance society. Educationalists have pointed out both chances for opening up and enhancing education and also tendencies of stupefaction, problematic power relations, or memory decline. Philosophers have eulogized or censored superficiality, social scientists have focused on networks as agency, the IT industry has made immediate availability a paradigm of development. Questions of archiving have often been overlooked, addressed within a conservative criticism of new media, or considered as a symptom of the historical disease at last to be left behind. Yet all of these approaches fail to do justice to the contemporary social, political, cultural and educational questions regarding the possibilities of digital archives. In the past few years manifold initiatives aiming at opening up education on various levels using digital communications technologies and Creative Commons licenses as well as massive open online courses (moocs) have been developed. Today, Open Educational Resources (OER) is widely used as an umbrella term for free content creation initiatives, OER Commons, Open Courseware (OCW), OER repositories, OCW search facilities, University OCW initiatives, and related activities. Among others, collections of shared resources such as Connexions, WikiEducator or Curriki have an ever-increasing number of visitors and contributors to the site. Just recently, an effort has been made with a view to mapping the landscape of institutional OER initiatives by the UNESCO/Commonwealth of Learning (COL) Chair. Against this background, this publication focuses on ongoing dynamics and transformational processes at the interfaces of OER initiatives and issues of digital archiving.